Менеджмент учебник - Песоцкая Е. В. Елена Владимировна; Русецкая О. В. Ольга Васильевна; Трофимова Л. А. Людмила Афанасьевна; Трофимов В. В. Валерий Владимирович; Петров А. Н. (Бакалавр)
На тит. л. и обл.: три автора